(untitled) (Law and world, 2018)
Self-defence is one of the ancient institutions of criminal law. Article 28 of Georgian criminal code defines basis for the self-defence. During qualification of self-defence, the most important aspect is proportionality of defence. The criminal code of Georgia defines general fundaments of proportionality. However, main point and criteria while qualification it detailed analysis of Georgia case law. In the research, we have discussed legal regulation of self defence, Georgian case law and statistic. According to the research we have suggested main criterias of qualification self defence proportionality.